Cytotoxic Activity and Apoptosis by Extract and Ethyl Acetate Fraction of Hibiscus tiliaceus Linn in 4T1 Cell Line - Hidayati, Devi Nisa; Safitri, Erika Indah; Surayya, Anis; Alviani, Dwi Lutvi; Putri, Masita Nur Amalia (Jurnal Kefarmasian Indonesia, 2024)
Waru leaves are proven to have cytotoxic activity. The activity of waru leaves needs to be developed in a molecular direction to see its apoptotic activity. This study aims to determine the cytotoxic activity of methanol extract (EWL) and ethyl acetate fraction fraction (EAFWL) of Hibiscus tiliaceus Linn as well as the induction of apoptosis in 4T1 cells. The methanol extract of hibiscus leaves was obtained by the maceration method, followed by a fractionation process with n-hexane, ethyl acetate, and water as solvents. Cytotoxic test of EWL was carried out at a concentration of 31.25; 62.5; 125; 250; 500 and 1000 μg/mL while EAFWL was at a concentration of 100; 200; 400; 600 and 100 μg/mL, using MTT assay. Analysis of IC50 values using linear regression. The apoptosis induction test at IC50 and ½ IC50 concentrations using flowcytometry. Data on the percentage of apoptosis were analyzed using One Way Anova statistical analysis. The results were EWL and EAFWL cytotoxic tests against 4T1 had IC50 values of 649 μg/mL and 746 μg/mL. EWL obtained a percentage of total apoptosis at a concentration of 324.5 μg/mL of 48.76%; 649 μg/mL was 67.06% and control cells were 36.16%. EAFWL percentage of total apoptosis at a concentration of 746 μg/mL of 30.8%; 373 μg/mL was 42.13% and control cells were 9.6%. So EWL and EAFWL can induce apoptosis of 4T1 cells.